The Crisis of Meaning in Modern Education: A Philosophical Dialogue between Western and Islamic Thought - Fuad, Nazhif Al; Azani, Mohammad Zakki (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Modern education faces a crisis of meaning characterized by the dominance of instrumental rationality, technocratization, and the reduction of educational goals to cognitive achievement and administrative performance. This condition causes education to lose its function as a process of holistic human formation— ethically, existentially, and spiritually. This study aims to analyze the crisis of meaning in education through a philosophical dialogue between Western and Islamic traditions, examining how both understand the goals of education and the formation of the human subject. The method used is qualitative library research based on an interpretive-hermeneutic paradigm. Primary data was obtained from the works of Western thinkers Dewey, Freire, Heidegger, and Islamic thinkers Al-Farabi, Ibn Sina, Al-Ghazali, Fazlur Rahman, Syed Muhammad Naquib al-Attas, while secondary data consisted of journal articles and contemporary academic works. The results of the study show that Western education emphasizes the formation of conscious, rational, free, and responsible subjects, but has experienced a narrowing of meaning due to technocratic pressures. Meanwhile, Islamic education emphasizes the formation of adab (ta'dīb), the integration of knowledge, ethics, and a transcendental orientation that guides humans to understand the purpose of life and their existential responsibilities. A synthesis of the two traditions shows that meaningful education is achieved through a balance between intellectuality and ethicality, critical reflection, and value orientation. These findings offer a philosophical framework for reformulating the goals of modern education as a process of understanding humans holistically from an Islamic perspective.